The european neighbourhood policy from the perspective of Azerbaijan economy - Oğuz, Süleyman (My University, 2006)
FROM THE PERSPECTIVE OF AZERBAIJANI ECONOMY ÖZET Tezin amacı Avrupa Komsuluk Politikası’nın Azerbaycan ekonomisi açısından muhtemel etkilerini incelemektir. Çalısmada, ekonomik beklentilerin yanısıra Komsuluk Politikası’nın Azerbaycandaki demokrasi ve insan hakları gelisimine olası katkıları da tartısılmıs, benzer sekilde Dağlık-Karabağ problemi açısından Komsuluk Politikası’nın değerlendirmesi yapılmıstır. Çalısmada kullanılan niteliksel çözümlemeye dayanarak Komsuluk Politikası’nın Azerbaycandaki ekonomik büyümeye pozitif etki yapacağı sonucuna varılmaktadır. Öte yandan, Avrupa Birliği’nin tarihsel olarak Azerbaycan’a yönelik olan benzer politikalarının basarısızlığı ve tutarsızlığı düsünülürse, Komsuluk Politikası’nın demokrasi ve insan hakları gibi değerlerin gelisimine katkısının öngörülen düzeyde gerçeklesmesinin süpheli olduğu ifade edilmektedir. Bundan baska, Komsuluk Politikası’nın bir anlasmazlık çözme aracı olarak gelistirilmediği dikkate alınırsa, Dağlık-Karabağ probleminin çözümü açısından bu Politika’nın katkısının sınırlı olacağı düsünülmektedir.

The purpose of the thesis is to examine the potential effects of the European Neighbourhood Policy (ENP) on the Azerbaijani economy. In addition to the economic implications, the study also discusses the ENP’s probable contribution to democracy and human rigths developments in Azerbaijan. Likewise, the thesis provides an assesment of the ENP from the perspective of Nagorno-Karabakh conflict. Based on a qualitative analysis, the ENP seems to have the potential to foster economic growth in Azerbaijan. The study identifies a number of ways through which this might happen, both directly through economic channels and indirectly, by providing support for proper structural and macroeconomic policies. The study also highlights a number of possible risks as supply-side specialisation and over-regulation . On the other hand, the intended EU contribution to democracy and human rights of Azerbaijan seems questionable, given that historically it was neither effective nor consistent in its related policies. Moreover, by considering the fact that the ENP is underdeveloped as a conflict resolution tool, the perspectives for the Nagorno-Karabakh conflict are limited.
Keywords: Avrupa Birliği_Dış İlişkiler_Azerbaycan; Avrupa Birliği_Ekonomi; Azerbaycan_Ekonomi